1983
DOI: 10.1093/bja/55.9.855
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Catecholamine Responses to Tracheal Intubation

Abstract: Plasma adrenaline and noradrenaline concentrations were measured in 24 patients during the induction of anaesthesia and the subsequent tracheal intubation. The patients received either suxamethonium 1 mg kg-1 or pancuronium 0.1 mg kg-1 to facilitate tracheal intubation. Mean arterial pressure (MAP) increased in both groups following laryngoscopy and tracheal intubation and there were concomitant increases in the plasma catecholamine concentrations, the changes being more marked in the suxamethonium group. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1
3

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(82 citation statements)
references
References 0 publications
5
73
1
3
Order By: Relevance
“…has been shown to provide sedation resulting in or from inhibition of CA release in conscious adults, 2~ it is unlikely that oral diazepam (10 mg) premedication attenuates CA changes following intubation in adults. [3][4][5] Thiamylal is a thiobarbiturate which is very similar to thiopentone in chemical structures and 1.1 times as potent as thiopentone. 2] Since two large-scale blinded studies found no difference between these drugs, ~ the difference in potency seems to be too small to achieve no clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…has been shown to provide sedation resulting in or from inhibition of CA release in conscious adults, 2~ it is unlikely that oral diazepam (10 mg) premedication attenuates CA changes following intubation in adults. [3][4][5] Thiamylal is a thiobarbiturate which is very similar to thiopentone in chemical structures and 1.1 times as potent as thiopentone. 2] Since two large-scale blinded studies found no difference between these drugs, ~ the difference in potency seems to be too small to achieve no clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples for the determination of hormonal stress response were taken from a separate intravenous cannula placed in the antecubital fossa after discarding 5 m l of blood at each timepoint. Derbyshire [3] demonstrated that central venous catheterisation is unnecessary when large changes in the catecholamine concentrations are expected and that sampling of blood from a large peripheral vein is acceptable .…”
Section: Study Protocolmentioning
confidence: 99%
“…8 Mean PTH concentrations in our patients increased in response to anesthetic induction ( Table 2). The catecholamine surge that occurs in response to tracheal intubation 9,10 has been shown to stimulate the PTH secretion. 11 Mahajna et al 11 reported a large increase in serum PTH in patients with normal parathyroid function; however, only female patients with primary HPT experienced a modest albeit statistically significant increase in serum PTH, while this increase was not significant in patients with secondary HPT.…”
Section: Discussionmentioning
confidence: 99%